THE ROLE OF INTRATUMORAL DENDRITIC CELLS IN THE PROGRESSION OF SQUAMOUS CELL CARCINOMAS - L. N. Bondar; L. A. Tashireva; O. V. Savenkova; E. L. Choynzonov; V. M. Perelmuter (Сибирский онкологический журнал, 2019)
The aim of the study was to summarize data on the role of tumor-associated dendritic cells (DC) in the formation of squamous cell carcinoma microenvironment, their participation in the development of immune inflammatory responses in the tumor stroma and relation to tumor progression.Material and Methods. We analyzed 79 publications available from Pubmed, Google Scholar, Elibrary databases from January 2000 to December 2017.Results. The characteristics of different types of DC, including Langerhans cells (CR), were presented. The different methods of DC identification were described. The information on the presence of DC in squamous cell carcinomas was analyzed. The influence of the tumor on DCs, as well as the relationship between the number and functional characteristics of DCs and invasive/metastatic tumor potentialities was described. The prognostic value of DCs and their effect on disease-free, metastasis-free and overall survival rates were analyzed. The data on the association between DCs and the response to chemoradiotherapy were presented. The analysis of the relationship between the DC characteristics and the development of immuno-inflammatory responses in the tumor microenvironment was carried out.Conclusion. The methodological approaches to the detection of DCs are variable, but the sensitivity of each method, as well as the comparison of different methods for estimating the number and functional characteristics of DCs, have been little studied. There is no data on the relationship between the length of DC dendrites and the parameters of invasive/metastatic tumor potentialities, disease-free, metastasis-free and overall survival rates. Numerous studies indicate the association between the number of DCs and the tumor progression, however these data are contradictory. There is no data about the relationship between the number of DCs and hematogenous metastasis of squamous cell carcinomas. The association of tumor-associated DC with the types of immunoinflammatory responses in the tumor microenvironment has been insufficiently studied.